UPAYA PENCEGAHAN PERUNDUNGAN DI SEKOLAH BAGI SISWA DI MI AL-FALAH JAKARTA - Indra Martha Rusmana; Nurhayati Nurhayati; Lasia Agustina (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Bullying is aggressive behavior carried out by a person or group of people who are strong, both physically and mentally, to others who are weaker. This aggressiveness is carried out repetitively and deliberately with the aim of hurting or weakening others. Bullying has actually been around since human civilization and is universal. Bullying can happen anytime, anywhere, by anyone, and against anyone including by and against elementary school students. The shape can also vary; It can be physical (such as pinching and hitting), verbal (such as teasing and mocking), social (such as silence and ostracism), or mental (such as glaring and looking sarcastically). Bullying can also manifest in the latest form according to current technological developments, namely cyber bullying. Basically, every child has different character traits. One of them is self-confidence. Children who have high self-confidence, then it is not difficult for them to socialize or adapt to a new environment. But on the contrary, children who have low or less self-confidence will find it difficult to adapt to their new environment, even they feel inferior, embarrassed, afraid, and become quiet. From this lack of confidence will bring out the attitude of others to disturb, prank, prank, etc. From the ignorance that others do, this can be said to be bullying. Bullying here can be done anytime and anywhere, and regardless of both men and associations. Both young children, adults, and the elderly, all can experience bullying, may be bullies or victims of the bullying. This is where the role of teachers is very necessary, especially in dealing with bullying in schools. How the teacher solves the case or problem that exists, then looks for the cause and effect of the occurrence of the case, as well as the best solution to the existing case and does not forget to encourage the victim of bullying not to feel inferior and provide direction, understanding and motivation to the bully that the actions he does are bad deeds and as much as possible instill in all to socialize about meaning bullying and its impact so that these students love each other without any persusushan